α-Tocopherol levels in natural and artificial aging of soybean seeds - doi: 10.4025/actasciagron.v34i3.12660 - Maria Izabel Krüger Giurizatto; Osvaldo Ferrarese-Filho; Maria de Lourdes Lucio Ferrarese; Antonio Dias Robaina; Manoel Carlos Gonçalves; Cláudia Andréia Lima Cardoso (Acta Scientiarum. Agronomy, 2011)
Tocopherols are well known constituents of vitamin E, and the main antioxidants in soybean. Are natural antioxidants and stabilizers that can inhibit lipid degradation, reducing non-enzymatic oxidation of these compounds during storage of seeds, germination and initial development of seedlings. The objective of this work was to determine the level of α-tocopherol in four soybean seeds cultivars naturally and artificially aged. Seeds of four soybean cultivars stored from 0 to 180 days in a dry chamber (natural aging) and subjected to high temperature and humidity (artificial aging) were analyzed for α-tocopherol content. The quantification of α-tocopherol in the soybean seeds was performed by high performance liquid chromatography (HPLC) combined with the Soxhlet extraction method. Significant differences in α-tocopherol levels in seeds were observed for all cultivars and storage times. The α-tocopherol contents of the soybean seeds showed linear correlations with an increasing period of storage for all the cultivars studied. However, the artificially aged seeds had a higher content of α-tocopherol than those naturally aged.